Cartografia de si: pistas possíveis para modos de presença na vida e na performance - Mendes Junior, Juscelino Ferreira (2020)
This research proposes to follow clues of a body in performance, crossed by encounters that transformed and composed a way of presence. It seeks to create relationships between performance practices that manage bodies in states of presence and how these states can generate ways of existence implied in creating their own lives. How do you compose possible modes of presence in the performance? How to map artistic processes that reveal other possibilities of relationship in the encounter? The investigation makes a cut in my artistic and performance practice of two years together with the collective and individual processes, and, also, with a field of poetic and artistic allies that compose an epistemological texture. I call on three collectives and performance artists active in Brazil: Grupo EmpreZa (GO), Berna reale (PA) and Ayrson Heráclito (BA), to create dialogues between their performances and a possible theoretical field about performative training, production of subjectivity and encounter in relation to studies on the presence and production of new ways of life. In addition to these, I bring three collective performances that took place over the years 2017 to 2019, two with the research group Asfalto - textures between arts and philosophy, namely: “Jardindigente (2017)” and “Buraco Negro (2017), and another with the extension project For a Clínica-Poética called “Qual vida queremos? Praia na UFU (2019)” that bring a little of the collective construction of such ways of presence. Finally, I present an individual performance called “Como se grita no escuro? (2019)” that presents a relationship with the Butoh dance and its possibilities for the production of life and ways of presence.